In Situ Laser Light Scattering for Temporally and Locally Resolved Studies on Nanoparticle Trapping in a Gas Aggregation Source. (28th July 2022) - Drewes, Jonas; Rehders, Stefan; Strunskus, Thomas; Kersten, Holger; Faupel, Franz; Vahl, Alexander
Abstract: Gas phase synthesis of nanoparticles (NPs) via magnetron sputtering in a gas aggregation source (GAS) has become a well‐established method since its conceptualization three decades ago. NP formation is commonly described in terms of nucleation, growth, and transport alongside the gas stream. However, the NP formation and transport involve complex non‐equilibrium processes, which are still the subject of investigation. The development of in situ investigation techniques such as UV–Vis spectroscopy and small angle X‐ray scattering enabled further insights into the dynamic processes inside the GAS and have recently revealed NP trapping at different distances from the magnetron source. The main drawback of these techniques is their limited spatial resolution. To understand the spatio‐temporal behavior of NP trapping, an in situ laser light scattering technique is applied in this study. By this approach, silver NPs are made visible inside the GAS with good spatial and temporal resolution. It is found that the argon gas pressure, as well as different gas inlet configurations, have a strong impact on the trapping behavior of NPs inside the GAS. The different gas inlet configurations not only affect the trapping of NPs, but also the size distribution and deposition rate of NPs. Abstract : The trapping of nanoparticles (NPs) inside a gas aggregation source is studied by in situ laser light scattering. Three different gas inlet configurations are investigated regarding dynamic NP trapping. It turned out that besides operation parameters like gas flow and pressure the gas inlet location also strongly affects the NP trapping position, size distribution, and deposition rate.